Abnormal thermal quenching and blue-shift of Zn3(BO3)(PO4):Inducing host defect by doping Mn2+ and Tb3+. (June 2019) - Liu, Simin; Wang, Zhijun; Bao, Qi; Li, Xue; Chen, Yun; Wang, Zhipeng; Guan, Li; Wei, Zhiren; Yang, Zhiping; Li, Panlai
Abstract: It is well-known that the thermal quenching (which is caused by non-radiative transition) damages the efficiencies of fluorescent lamps and LED lamps, especially for the high-power devices. Therefore, it is important to reduce the thermal quenching for improving the performance of illumination devices. In this work, Zn3 (BO3 )(PO4 ):Mn 2+, Tb 3+ is designed which appeared abnormal thermal quenching behavior. The phosphor does not exhibit thermal quenching even up to 200 °C (for emission of Mn 2+ ) and 150 °C (for emission of Tb 3+ ). The abnormal phenomenon is related to the shallow effects which are caused by the Mn 2+ and Tb 3+ doping in the host. Meanwhile, the thermal active phonon-assisted excitation also prevents the thermal quenching, which results in the broadening and blue-shift of the emission bands. Our result demonstrated that Zn3 (BO3 )(PO4 ):Mn 2+, Tb 3+ may be a potential candidate for the exploration of thermal stable materials. Graphical abstract: Image 1 Highlights: Zn3 (BO3 )(PO4 ):Mn 2+, Tb 3+ was synthesized by solid state method. An abnormal phenomenon is related to the defect of the host. Thermal stability of phosphor was improved.